Control strategy and parameter setting for wind power considering secondary frequency drop - Chao Zhang; Yunfeng Wen; Jingxian Li (International Journal of Electrical Power & Energy Systems, 2025)
The variability of wind power impacts its frequency support capability. To enhance the stability and reliability of frequency support from doubly fed induction generator-based wind farms (DFIG-based WFs) during the primary frequency regulation process, this paper first introduces a frequency support control strategy of DFIG-based WFs that emphasizes a smooth recovery of rotational speed. Once the system frequency reaches its nadir, DFIG-based WFs adaptively reduce their active output to enter a rotational speed recovery state. Concurrently, the frequency support control parameters are adjusted based on the recovery conditions, mitigating the negative effects of speed recovery on system frequency. Then the kinetic energy for frequency support of DFIG-based WFs at various speeds is calculated based on the operating point deviations during the frequency support process. Following this, we derive the time domain expression of the system frequency response model, which incorporates the participation of synchronous generators and wind power in frequency support. The formula for calculating the maximum frequency deviation under different damping ratios is also unified. Furthermore, an optimization model is established based on frequency security constraints and maximum frequency support energy constraints, with the objective of minimizing the frequency support requirements from DFIG-based WFs. The time of the frequency nadir during fault scenarios and the frequency control parameters for each wind farm are calculated to establish the control parameters for each farm. Finally, the efficacy of the proposed control strategy and parameter setting model is validated through simulation examples involving the IEEE 39-bus system and a provincial power grid.